2007
DOI: 10.1177/154193120705101704
|View full text |Cite
|
Sign up to set email alerts
|

Office chairs are often not adjusted by end-users

Abstract: To find out how many office workers adjust their chairs, 350 office workers in Spain and the Netherlands are observed and questioned on whether they adjust their chairs. It appears that 24% of 236 Spanish office workers and 61% of 100 Dutch subjects never adjust their chair. If the chair is adjusted, it concerns mostly the seat height. Except for the seat height, other adjustment possibilities are not used by the majority of the study population. Reasons for not adapting could be awareness, complexity of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…When provided with a new office chair, the worker may seek to make certain immediate adjustments to it to optimize it for their body size and comfort. The need to provide adequate support for the feet on the floor, for example, may promote a search for the seat height control (Vink et al, 2007). Indeed Groenesteijn et al (2009a) found that chair adjustment was more common in initial chair use compared with later use.…”
Section: Office Chair Adjustment Driversmentioning
confidence: 99%
See 4 more Smart Citations
“…When provided with a new office chair, the worker may seek to make certain immediate adjustments to it to optimize it for their body size and comfort. The need to provide adequate support for the feet on the floor, for example, may promote a search for the seat height control (Vink et al, 2007). Indeed Groenesteijn et al (2009a) found that chair adjustment was more common in initial chair use compared with later use.…”
Section: Office Chair Adjustment Driversmentioning
confidence: 99%
“…Individual differences and increased workforce diversity suggest that sitting in a chair previously adjusted for someone else's body size and working needs may result in physical discomfort (from an excessively high seat pan, for example) which may drive some chair adjustment behavior. Vink et al (2007) suggested that many office chairs are designed without realistic knowledge of their users, and users are presumed to possess knowledge they do not have. Indeed, the presence of a highly adjustable chair is no guarantee its user has been trained to use itor does.…”
Section: Office Chair Adjustment Driversmentioning
confidence: 99%
See 3 more Smart Citations